Core Competencies: Concept and Relevance - Gupta, R. K. (Prabandhan: Indian Journal of Management, 2013)
The concept of ’Core Competencies’ was first proposed by Prof. Gary Hamel and Prof. C.K. Prahalad in 1990 to deliver sustainable competitive advantage. This paper reports a part of the research conducted on a sample of selected listed Indian companies on "Factors Determining Excellence In Business - A Study of Selected Listed Companies In India". However, a few companies in the sample - that represented the top performing companies - indicated that they had identified their core competencies. The concept of core competency may well become a trap of false security unless it is understood in the right context. The core competencies have to be viewed in context of future competition and have to be well integrated with product-market strategy. The paper examines the various aspects of core competencies by critically examining various issues related to assessing, developing, and utilizing such competencies for achieving business excellence. The paper explains the issues with several examples of Indian and foreign companies that makes the reader grasp the concept easily. The present paper concludes that the right bundle of core competencies do act as a crucial factor for business excellence.